Factors affecting offshore fishing households’ income in southern central coast of Vietnam - Hiep Hong Hoang; Tam Bang Vu; Hanh Viet Ho; Hung Tuan Vu; Quang Dai Nguyen (Management Science Letters, 2019)
This paper uses econometrics models to estimate factors affecting the offshore fishing households’ incomes in the Southern Central Coast of Vietnam. We estimate two basic models: one with total income as the dependent variable and the other with per capita income as the dependent variable. Since heteroscedasticity is in present, the study employs Ordinary Least Squares (OLS) estimations with Robust Standard Errors (OLSR). The models are further divided into a model with intercept dummies and the one with slope dummies. The estimation results for the intercept dummies indicate that fishing technology, number of days per trip, type of fishery, the residential characteristics, household size, number of dependents, captains' experience, fishing ground, consumer market, and the role of officers for fishing stimulation are the main factors having significant impacts on fishing household’s income. Surprisingly, ship capacity, income diversification, career passion, householder’s educational background, and consumer market have no significant impact on fishing household’s income. The results for the intercept and slope dummies, both, indicate that the Southern areas enjoy more benefits than the Northern areas in terms of income and utilizing the stimulation policies. The empirical results allow us to suggest some policy recommendations for central and provincial government aiming at improving offshore fishing household’s income in the Southern Central Coast of Vietnam.